The spatiotemporal response of land-use carbon emissions to climate change - Shenjie Yang; Lanjiao Wen; Anlu Zhang (Ecological Indicators)
Land-use carbon emissions (LUCEs) are the second source of anthropogenic carbon emissions and need to be curbed by efficient treatment. Given the impacts of climate change on ecosystems and human activities, it is crucial to understand its effects on LUCEs. Using China as a case study, this study measures climate change by using temperature anomalies (TA) and precipitation anomalies (PA). A geographically and temporally weighted regression (GTWR) model is used to explore the spatiotemporal response of LUCEs to TA and PA across 30 provinces from 2000 to 2020. The results show that the impacts of both TA and PA on LUCEs shifted from negative to positive from 2000 to 2020 with the influence of TA increasing significantly since 2015. Positive effects of TA are mainly concentrated in the northern and south-central regions, and negative effects are concentrated in the south-central, eastern, and parts of the southwest regions. The negative impacts of PA on LUCEs are mostly located in the southwest and northern regions, while the positive impacts are found in the south-central and northern region. The findings suggests that climate variability can exacerbate both direct and indirect carbon emissions resulting from land use. Local governments should adopt appropriate land-use measures to cope with climate change in land-use systems.